Sobre a morte e o morrer: concepções e paralelismos entre o catolicismo romano e o budismo tibetano - Henriques, Ana Cândida Vieira (2014)
Religion as an object of study is constituted by providing an endless universe of knowledge, in which the religious phenomenon becomes open to a scientific look. Within this scenario we place the death that comes in its universal aspect. This way, our research is based on a comparative study in which we intend to analyze the structures that comprise the phenomenon of death in two traditions, the Roman Catholicism and the Tibetan Buddhism, both inserted in Christianity and Buddhism, two of the five major religions of the world. We will hold on to expose conceptions and visions of death in the historical development, the ritualization of death and its transformation, the funerary practices that give meaning to death and beliefs in the afterlife in both doctrines. In these two very broad and complex religious systems, we will deal specifically with the topic of death, aiming to analyze them in relation to their distinct and similar elements, from scientific and theological presuppositions, using religious and philosophical conceptions based on reliable sources of both traditions. Concerning to the Roman Catholicism, we will use the Catechism of the Catholic Church and the book of funerals, and referring to the Tibetan Buddhism, we will use as the main source, the Tibetan Book of the Dead. We will use as bibliographic source, the thinking of various scholars about the knowledge of death and its implications for society